2017^10 +1 / 2017^9 +1 và 2017^11 +1 / 2017^10+1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : \(A=\frac{10^{2016}-1}{10^{2017}-11}\)
\(\Leftrightarrow10.A=\frac{10.\left(10^{2016}-1\right)}{10^{2017}-11}=\frac{10^{2017}-10}{10^{2017}-11}\)
\(=\frac{10^{2017}-11+1}{10^{2017}-11}=1+\frac{1}{10^{2017}-11}\)
Lại có : \(B=\frac{10^{2016}+1}{10^{2017}+9}\)
\(\Leftrightarrow10.B=\frac{10\left(10^{2016}+1\right)}{10^{2017}+9}=\frac{10^{2017}+10}{10^{2017}+9}\)
\(=\frac{10^{2017}+9+1}{10^{2017}+9}=1+\frac{1}{10^{2017}+9}\)
Do : \(10^{2017}-11< 10^{2017}+9\) \(\Rightarrow\frac{1}{10^{2017}-11}>\frac{1}{10^{2017}+9}\)
\(\Rightarrow1+\frac{1}{10^{2017}-11}>1+\frac{1}{10^{2017}+9}\)
hay \(A>B\)
Vậy : \(A>B\)
Ta có:
\(\frac{2017^{10}+1}{2017^{10}-1}=1+\frac{2}{2017^{10}-1}\)
Lại có:
\(\frac{2017^{10}-1}{2017^{10}-3}=1+\frac{2}{2017^{10}-3}\)
Vì \(1+\frac{2}{2017^{10}-1}< 1+\frac{2}{2017^{10}-3}\)
Nên \(\frac{2017^{10}+1}{2017^{10}-1}< \frac{2017^{10}-1}{2017^{10}-3}\)
Vậy \(\frac{2017^{10}+1}{2017^{10}-1}< \frac{2017^{10}-1}{2017^{10}-3}\)
Ta có
\(\frac{2017^{10}+1}{2017^{10}-1}=\frac{2017^{10}-1+2}{2017^{10}-1}=1+\frac{2}{2017^{10}-1}\)
\(\frac{2017^{10}-1}{2017^{10}-3}=\frac{2017^{10}-3+2}{2017^{10}-3}=1+\frac{2}{2017^{10}-3}\)
\(\Rightarrow1+\frac{2}{2017^{10}-1}< 1+\frac{2}{2017^{10}-1}\)
\(\Rightarrow\frac{2017^{10}+1}{2017^{10}-1}< \frac{2017^{10}-1}{2017^{10}-3}\)
Có \(A=\frac{10^{2017}+1-3}{10^{2017}+1}=1-\frac{3}{10^{2017}+1}\)
\(B=\frac{10^{2017}+3-3}{10^{2017}+3}=1-\frac{3}{10^{2017}+3}\)
Có 102017+1<102017+3
=> \(\frac{3}{10^{2017}+1}>\frac{3}{10^{2017}+3}\)
=>A<B
Vì \(A=\dfrac{10^{2017}-2}{10^{2017}+1}< 1\)
\(\Rightarrow B=\dfrac{10^{2017}-2}{10^{2017}+1}< \dfrac{10^{2017}-2+2}{10^{2017}+1+2}=\dfrac{10^{2017}}{10^{2017}+3}=A\)
Vậy A > B
Vì \(A< 1\)
\(\Rightarrow A< \dfrac{10^{2017}-2+2}{10^{2017}+1+2}=\dfrac{10^{2017}}{10^{2017}+3}=B\)
Vậy A < B